2013
DOI: 10.2337/db12-0255
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Adipose Tissue De Novo Lipogenesis in Glucose Homeostasis During Catch-up Growth

Abstract: Catch-up growth, a risk factor for type 2 diabetes, is characterized by hyperinsulinemia and accelerated body fat recovery. Using a rat model of semistarvation-refeeding that exhibits catch-up fat, we previously reported that during refeeding on a low-fat diet, glucose tolerance is normal but insulin-dependent glucose utilization is decreased in skeletal muscle and increased in adipose tissue, where de novo lipogenic capacity is concomitantly enhanced. Here we report that isocaloric refeeding on a high-fat (HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 38 publications
1
52
0
2
Order By: Relevance
“…This evidence supports the hypothesis that early catch-up fat of the H1N offspring is not associated with overt adipocyte hypertrophy or inflammation. 68 These results suggested that a preweaning H1N diet programmed the pathophysiological changes of adipose tissue at least partially through the upregulation of genes involved in adipogenesis and lipogenesis.…”
Section: Discussionmentioning
confidence: 87%
“…This evidence supports the hypothesis that early catch-up fat of the H1N offspring is not associated with overt adipocyte hypertrophy or inflammation. 68 These results suggested that a preweaning H1N diet programmed the pathophysiological changes of adipose tissue at least partially through the upregulation of genes involved in adipogenesis and lipogenesis.…”
Section: Discussionmentioning
confidence: 87%
“…FAS activity was assessed in e-WAT since previous results have shown a downregulation of its activity in this specific fat pad in rats refed with SFA-MUFA diet (Marcelino et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Recent work demonstrates that adipose tissue DNL is important in regulating glucose homeostasis ( 40 ). While glucose is thought to be the major precursor for DNL when mice are fed a diet high in carbohydrate, as much as one-third of TG/glycerol can be derived from nonglucose sources (i.e., glyceroneogenesis via PEPCK) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%